2021
DOI: 10.3389/fphys.2021.620201
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Short-Term Warm Water Immersion on Arterial Stiffness and Central Hemodynamics

Abstract: Warm water immersion (WWI) has a potentially favorable effect on vascular health. However, the effects of short-term WWI on vascular function and central hemodynamics remain unclear. The present study aimed to determine the acute effects of short-term WWI on arterial stiffness and central hemodynamics in healthy men. Ten healthy men (27–57 years, 44 ± 12 years of mean age) underwent 5-min WWI (40–41°C) at the heart level. Systemic hemodynamics and tympanic temperature were monitored during WWI. Furthermore, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The present findings of local stiffness are in agreement with past whole body and two leg hyperthermia studies which reported no changes in regional (carotid–radial) arterial stiffness (Ganio et al, 2011 ; Moyen et al, 2016 ; Schlader et al, 2019 ). However, studies exploring the recovery following hyperthermia, reported decreases in peripheral and/or leg (femoral–ankle region) arterial stiffness alongside an elevated core temperature (Caldwell et al, 2017 ; Cheng et al, 2021 ; Lee et al, 2018 ; Sugawara & Tomoto, 2021 ; Thomas et al, 2017 ). The latter observations contrast with the unaffected or small changes in arterial stiffness/distensibility, core temperature, and arterial pressure observed in the present and previous single leg heating studies (Chiesa et al, 2015 , 2016 ; Engelland et al, 2020 ; Takahashi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings of local stiffness are in agreement with past whole body and two leg hyperthermia studies which reported no changes in regional (carotid–radial) arterial stiffness (Ganio et al, 2011 ; Moyen et al, 2016 ; Schlader et al, 2019 ). However, studies exploring the recovery following hyperthermia, reported decreases in peripheral and/or leg (femoral–ankle region) arterial stiffness alongside an elevated core temperature (Caldwell et al, 2017 ; Cheng et al, 2021 ; Lee et al, 2018 ; Sugawara & Tomoto, 2021 ; Thomas et al, 2017 ). The latter observations contrast with the unaffected or small changes in arterial stiffness/distensibility, core temperature, and arterial pressure observed in the present and previous single leg heating studies (Chiesa et al, 2015 , 2016 ; Engelland et al, 2020 ; Takahashi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hyperthermia may directly act on the conduit artery supplying blood to the heated region by increasing arterial stiffness/decreasing arterial distensibility rather than altering diameter, as seen during incremental exercise (Pomella et al, 2018 ). The current literature suggests that central and/or regional arterial stiffness is unchanged during acute hyperthermia (Ganio et al, 2011 ; Moyen et al, 2016 ; Schlader et al, 2019 ) and declines following the cessation of heating (Lee et al, 2018 ; Sugawara & Tomoto, 2021 ; Thomas et al, 2017 ). To our knowledge, however, no study has explored the effects of hyperthermia on arterial distensibility using local techniques—such as the PU ‐loop or ln( D ) U ‐loop (Feng & Khir, 2010 ; Khir et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immersion can also be in a standing position ( Prefaut et al, 1976 ; Leeder et al, 2015 ) or sitting ( Leeder et al, 2015 ). The temperature of the immersion medium can be cold ( Sánchez-Ureña et al, 2018 ; Ihsan et al, 2020 ; Kositsky and Avela, 2020 ) or warm ( An et al, 2019 ; Sugawara and Tomoto, 2021 ). Immersion can be for the entire body with the head ( Elia et al, 2021 ) or a part of the body ( Roberts et al, 2015 ; Engelland et al, 2020 ).…”
Section: Dry Immersionmentioning
confidence: 99%
“…En el caso de la técnica del paño, la temperatura disminuye cuando se aplica el paño en las zonas de mayor irrigación sanguínea permitiendo que por medio de la osmosis se transfiera este calor hacia el exterior, específicamente el paño o compresa utilizada (24). Por otro lado, en la técnica 2 de baño se sumerge al niño en una tina de agua tibia a una temperatura de 35ºC, frotando con un paño todo el cuerpo, durante 15 o 20 minutos (25); es decir, según la física las cargas eléctricas del mismo signo se repelen (26), junto con la fricción que se ejerce entre los dos objetos existe un aumento de calor (27), dando un efecto de vasodilatación a los vasos sanguíneos permitiendo que salga el calor y provoque enfriamiento a través de la convección. Este mecanismo consiste en la transferencia de calor desde el cuerpo hacia otras partículas libres que se encuentran en el ambiente como el agua, misma que se aplicó en la investigación cuando se sumerge al individuo en agua tibia (2).…”
Section: Discussionunclassified